РОЛЬ ИЗУЧЕНИЯ ИНОСТРАННЫХ ЯЗЫКОВ В ПРОЦЕССЕ ИНТЕРНАЦИОНАЛИЗАЦИИ ВЫСШЕГО ОБРАЗОВАНИЯ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The state reveals such important aspects as the concept of language, we find answers to questions like language, language functions, classification of languages. The role of learning foreign languages in the modern world. This scientific article is written with the aim of drawing attention to the true nature of learning foreign languages in the modern world.
Keywords: foreign languages, role, meaning, importance, peculiarity, higher education, linguistics, opportunities.